Desorption and Re-Adsorption of Procion Red MX-5B Dye on Alumina-Activated Carbon Composite - Fatma Fatma; Poedji Loekitowati Hariani; Fahma Riyanti; Wiwin Sepriani (Universitas Gadjah Mada, 2018)
The alumina-activated carbon has the ability to adsorb and desorb the procion red MX-5B. The research evaluated the influence of desorption agent, contact time, and temperature on desorption process of procion red MX-5B dye with alumina-activated carbon composite and the adsorption capacity of the composite after desorption process. The desorption agents used in desorption process were solution with pH 2−10, H2O2 30 % (v/v), methanol 70% (v/v) and ethanol 70% (v/v). The variation of contact time was in the range from 30 to 270 min and the temperature was set between 30−75 °C. The result concluded that the highest desorption efficiency up to 98.56% was achieved using ethanol 70% (v/v) for 240 min at 45 °C. The desorption kinetic followed the pseudo-first-order with the release constant (kdes) of 6.56 × 10-2 min-1. The SEM micrograph showed there is a more porous surface on the composite after the desorption compared to before the desorption. The EDX analysis indicated that alumina content in the composite was reduced after desorption process. FTIR spectra of the composite before and after desorption process showed a peak of Al−O at 592 and 590 cm-1 which was proved that alumina still exists in the composite after the desorption process. The alumina-activated carbon composite was re-used to adsorb procion red MX-5B dye. After three times of desorption and re-adsorption process, the capacity adsorption was decreased from 12.38 to 7.38 mg/g.